Diagnostic value of the pregnancy index for acute appendicitis in pregnant women - Ismail Sezİklİ; Ramazan Topcu; Mehmet Berksun Tutan; Orhan Aslan; Mahmut Arif Yüksek (Scientific Reports)
Abstract Acute appendicitis is one of the most common non-gynecological and non-obstetric causes of acute abdominal conditions requiring urgent surgery during pregnancy. Due to the similarity between the symptoms of the disease and those of pregnancy, laboratory findings become particularly important in diagnosis. This study aimed to evaluate these parameters for the first time using a new index definition. Between 2015 and 2021, a total of 120 patients were included in the study, divided into the four groups: healthy pregnant woman (HPW), healthy woman (HW), unhealthy pregnant woman (UPW, pregnant patient with acute appendicitis), and unhealthy woman (UW, non-pregnant patient with acute appendicitis). Laboratory parameters, including white blood cell count (WBC), C-reactive protein (CRP), neutrophil-lymphocyte ratio (NLR), ischemia-modified albumin (iMA), and platelet-lymphocyte ratio (PLR), were assessed. In this study, significant differences were observed in various laboratory parameters between groups, such as WBC, CRP, NLR, and PLR, indicating potential markers for differentiating between pregnant women with and without appendicitis. An index was created for the diagnosis of acute appendicitis in pregnant women and was named the Pregnant Index. The Pregnant Index (PGIndex) values of pregnant women without appendicitis were compared with those of pregnant women with appendicitis. It was found that the PGIndex value was significantly higher in pregnant women with appendicitis (p < 0.001). Using the ROC curve and Youden index, the PGIndex cut-off value to best differentiate between the two groups was 10.62. This value provided a sensitivity of 73.3%, specificity of 96.7%, positive predictive value of 95.7%, negative predictive value of 78.7%, and test accuracy of 85% for identifying pregnant women with appendicitis. Compared to other markers, the PGIndex had the highest accuracy value, and it was observed that patients with a PGIndex value above 10.62 had a significantly increased likelihood of having appendicitis. These results indicate that the PGIndex is a significant marker for detecting appendicitis in pregnant women. Laboratory parameters, particularly NLR and PLR, show promise as diagnostic tools for appendicitis in pregnant women. Incorporating these markers, the Pregnant Index (PGIndex) demonstrated high sensitivity and specificity in distinguishing between pregnant women with and without appendicitis. This is the first study using the Pregnant Index in pregnant women to diagnose appendicitis. Early diagnosis is crucial for preventing maternal and fetal morbidity and mortality associated with appendicitis during pregnancy.